Gut Microbiota and Short-Chain Fatty Acid Profile between Normal and Moderate Malnutrition Children in Yogyakarta, Indonesia - Rafli Zulfa Kamil; Agnes Murdiati; Mohammad Juffrie; Jiro Nakayama; Endang Sutriswati Rahayu (Microorganisms, 2021)
Malnutrition has been associated with the gut microbiota composition and the gastrointestinal environment. This study aimed to evaluate whether there is a difference in the gut microbiota profile between the normal and undernutrition (considered moderate malnutrition) children and evaluate the gastrointestinal environment observed from the short-chain fatty acid (SCFA) profile. Ten days’ observations were done between normal (n:13) and undernutrition (n:15) children. The subject’s diet was recorded using a food record. Analysis of the gut microbiota was performed using 16S rRNA gene sequencing targeting the V3-V4 variables region, while the SCFA profile was analyzed using gas chromatography. The result shows that the undernutrition group’s energy intake was lower than in the normal group. Although there was no difference in diversity index and overall gut composition, overexpression of the genera Methanobrevibacter, Anaerococcus, Eubacterium, and Succinivibrio was observed in the undernutrition group. Meanwhile, in the normal group, Ruminococcus and Fusobacterium were found. In both groups, there was also the dominant of Prevotella enterotype. Gastrointestinal conditions in the normal group tended to be more acidic compared to the undernutrition group. It occurs due to the high concentration of propionate and butyric acids.